Nutritional Profile Of Institutional Elderly And Feasibility In Use Of Red Palm Oil In Their Diets ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2015)
Objective: The nutritional status of institutionalized elderly, their health behavior and related socio  economic factors affecting their nutrition and feasibility of using red palm oil in the diets of inmates  was investigated in present study. Methods: The sample comprised of 100 elderly from St. Mary's  Home Arya Mahila Ashram and Sandhya Home, New Delhi. The subjects were divided into 2 age  groups namely 60-69 years and ≥ 70 years. The nutritional status was assessed using interview and  observation method. The techniques employed were dietary survey, anthropometry, clinical  examination, blood pressure, and hemoglobin and blood glucose measurement. The feasibility of  using red palm oil was determined by sensory evaluation method. Results: The subjects had very  strong food preferences and beliefs which affected their dietary intake. The mean daily of energy and  other nutrients except iron and Vitamin 'A' was adequate. Protein and retinol intakes were  significantly different among residents of three institutions. The mean weight, height, mid upper arm  circumference and total arm length for 60-69 years and ≥ 70 years men were 62.0kg, 156.8cm,  24.3cm, 63cm, 50.7cm and 63.1kg, 157.5cm, 25.3cm, 74.9cm and 52.3cm respectively. The  corresponding values for woman were 61.8kg, 154.8cm, 25.7 cm, 81.3cm, 53cm and 56.4kg,  152.7cm, 24.2cm, 78.6cm, 51.4cm respectively. A significant correlation between the total arm  length and height was observed. Six percent of the population was hypertensive 70% anemic and  49% had high blood glucose level. Red palm oil was well accepted by the inmates of St Mary Home  when used in 'dhal' vegetable preparation, "parantha" and suji halwa. Conclusion: The state of  institutionalized elderly in the present study was good as institutions were taking care of at least their  basic needs of food, clothing and shelter. A variety of programs like cultural, informative and  interactive should be planned to keep them mentally and socially occupied. Since the elderly in the  old age homes were having inadequate beta carotene, inclusion of foods like red palm oil by the  management may be good idea.
Keywords: Elderly; Female; Institutionalized; Nutritional Status